The Statistical Analysis on Physical and Rheological Properties of the Bitumen Modified with CR+SBS+Sasobit - Erkus, Yunus; Kök, Baha Vural (My University, 2023)
In this study, crumb rubber (CR), styrene-butadiene-styrene (SBS) and warm mix additive (Sasobit) modified bitumen binders were statistically investigated. The data set consisting of 32 binders modified by pure, CR, SBS, Sasobit and CR+SBS+Sasobit was studied. While additive ratios were defined as independent variables, results obtained from softening point, viscosity, dynamic shear rheometer and bending beam rheometer experiments were defined as dependent variables. Experiment results were analyzed individually and collectively using response surface methodology and pearson correlation methods. When the experiments were evaluated individually, very important relationships were found between additives rates and all experimental results. Actual values and estimated values obtained as a result of statistical analysis overlapped. It was determined that there were strong relationships between all experimental results when the pearson correlation between the experimental results was examined. Optimization was made according to the test results where the viscosity of 3000 cP (suitable workability), softening point and dynamic shear rheometer test results were maximum (superior high temperature performance) and the test result of bending beam rheometer was minimum (superior low temperature performance). According to this, CR, SBS and Sasobit rates were determined as 5.6%, 4% and 1%, respectively.
Keywords: Bitumen; crumb rubber; styrene-butadiene-styrene; Sasobit; statistics.